Role of PET/CT in initial staging and follow up of soft tissue and osseous sarcomas - Nehal Ali Abdelmohsen; Heba Kamal Ali; Manar Hussein Abdelsattar (Cairo : Nehal Ali Abdelmohsen, 2016)
Bone and soft tissue sarcomas are rare malignant tumors. They are a heterogeneous group of mesenchymal malignancies arising from bone and soft tissues. Primary bone tumors are seen more commonly in adolescents and younger adults, while primary soft tissue sarcomas are seen more commonly in adolescents with a second peak in the fifth decade. However, these sarcomas can affect all age groups. Diagnosis of musculoskeletal tumors is usually established on the basis of directed biopsies after the detection of a mass on clinical exam and/or imaging. The management of the patients depends on accurate staging of tumor spread, the identification of nodal involvement and distant metastases, which is important at diagnosis, assessing treatment plans, determining prognosis and evaluating response to treatment
Thesis (M.Sc.) - Cairo University - Faculty of Medicine - Department of Radio-diagnosis
Issued also as CD
Keywords: Osseous sarcomas; PET/CT; Soft tissue